+0  
 
0
40
1
avatar+133 

Given the system of equations \(\begin{align*} xy &= 6 - 2x - 3y,\\ yz &= 6 - 4y - 2z,\\ xz &= 30 - 4x - 3z, \end{align*}\)find the positive solution of x.

 May 19, 2020
 #1
avatar+111321 
+2

xy  = 6 - 2x - 3y                     xz  =   30  - 4x   - 3z

xy + 3y  =  6 - 2x                   xz + 3z  =  30 - 4x

y ( x + 3)  = 6  - 2x                z( x + 3)  = 30 - 4x

y =  (6 - 2x) / ( x + 3)             z =  ( 30 - 4x) / ( x + 3) 

 

yz  =  6 - 4y - 2z

 

(6 - 2x) /( x + 3)  *  (  30 - 4x)/ (x + 3)   =   6   - 4 (6 - 2x)/(x + 3 )  - 2 ( 30-4x)/ ( x + 3)

 

Multiply  through  by (x + 3)^2

 

(6- 2x)  * (30 - 4x)  =  6 ( x + 3)^2   - 4 (6-2x)(x + 3)  - 2(30-4x)(x + 3)   

 

180 - 84x + 8x^2   =  6(x^2 + 6x + 9)  - 4(6x - 2x^2 + 18 - 6x)  - 2 ( 30x - 4x^2 + 90 - 12x)

 

180 - 84x  + 8x^2  =  6x^2 + 36x + 54  - 24x + 8x^2 - 72 + 24x  - 60x + 8x^2 - 180 + 24x

 

Simplify

 

180 - 84x  + 8x^2  = 22x^2   -198

 

14x^2  + 84x - 378  =  0           divide through by 14

 

x^2  + 6x  -  27  =  0      factor

 

(x - 3) ( x + 9)  =  0

 

The positive solution is   x  -3   = 0    ⇔   x  =  3

 

 

cool cool cool

 May 19, 2020

2 Online Users